The Developmental State in the 21st Century: A Critical Analysis and a Suggested Way Forward - Karaoğuz, Hüseyin Emrah (Panoeconomicus, 2022)
A vast literature has accumulated on the developmental state since its introduction to scholarship in the 1980s. Despite many criticisms, developmental state is still the most viable alternative to the orthodoxy in the eyes of many. This article analytically investigates the sources of pessimism and optimism in the building of 21st century developmental states. The study notes that although there are sound reasons to be pessimistic regarding the emergence of successful cases in the new millennium, there are also reasonable grounds to be optimistic. A complex dynamic within and between domestic and international spheres determines the outcome, but there is no reason to disregard prematurely or embrace indisputably the developmental state construct. Key words: Political economy, Developmental state, Economic development. JEL: O20, O57, P16.